From Trophy Towns to City-States : Urban Civilization and Cultural Identities in Roman Pontus - Madsen, Jesper Majbom (Empire and After Ser, 2020)
Cover -- From Trophy Towns to City-States -- Title -- Copyright -- Contents -- Introduction -- Chapter 1. The Eternal Hunt for Glory -- Chapter 2. Building Cities from the Ground -- Chapter 3. Introducing Civic Life -- Chapter 4. Eager to Be Both Greek and Roman -- Conclusion -- Notes -- Bibliography -- Index -- Acknowledgments.